Nuevo surfactante en el control e inhibición de asfaltenos en un pozo-yacimiento - Ramírez Pacheco, Carlos (My University, 2012)
Nuevo surfactante en el control e inhibición de asfaltenos en un pozo-yacimiento
Nuevo surfactante en el control e inhibición de asfaltenos en un pozo-yacimiento
Keywords: Nuevo surfactante en el control e inhibición de asfaltenos en un pozo-yacimiento